Evaluation of some haematological, liver, and renal function biomarkers in different job categories at Kufa cement factory workers: a cross-sectional study - Farah Shaker Abdel Wahed; Zaid Makki Mohammed Al-Hakkak (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the workplace health-related environment of workers in various job categories at a cement factory. Method: The cross-sectional study was conducted at the Kufa Cement Factory, Najaf, Iraq, from November 12, 2021, to January 12, 2022, Kufa Cement Factory in Iraq, and comprised adult male non-smoking factory workers in group A, and healthy, unexposed non-smokers in control group B. Subjects in group A were subdivided into factory, kiln and packing workers. All the participants were subjected to blood tests for liver and kidney functions. Data was analysed using SPSS 27. Results: Of the 90 subjects, 45(50%) were each of the 2 groups. The mean age of group A workers was 46.581±1.559 years and they had a mean duration of exposure 15.953±0.873 years. There were 15(33.3%) factory workers and as many kiln and packing workers. Group A subjects worked for at least 7-8 hours per day. The subjects in control group B had a mean age of 45.01±8.17 years and were matched for gender. There was significant elevation in total leukocyte count, alkaline phosphatase, aspartate aminotransferase and alanine aminotransferase in group A compared to group B (p<0.05). Neutrophils were significantly high in factory workers than controls and packing workers (p<0.05), while total bilirubin level was significantly high in factory and kiln workers than controls (p<0.05). There was no significant difference in the mean serum creatinine level between the groups (p>0.05). Conclusion: Workplace exposure to cement particulate in a factory environment was found to have a harmful impact on health. Key Words: Alanine Transaminase, Alkaline Phosphatase, Creatinine, Neutrophils, Liver, Leukocyte, Aspartate Aminotransferases, Hematologic, Bilirubin, Kidney